Copper-squirrel-cage Solid Rotor Teeth Zone Parameter Rational - Gečys, S.; Smolskas, P. (Elektronika ir Elektrotechnika, 2009)
The optimization of copper-squirrel-cage solid rotor geometry of the small power induction motors, operating in borehole investigation devices while considering the parameters of the supply circuit and the motor equivalent circuit, is studied. The optimization criterion is the comparison of the copper-squirrel-cage solid rotor equivalent resistance to the supply circuit resistance taking into account the following limitations: the minimum copper-squirrel-cage solid rotor leakage reactance; the maximum value of rotor tooth magnetic flux density. The same stator was used in all optimization calculations in order to achieve comparable results. The maximum value of average electromagnetic torque as a function of rotor slot (tooth) depth and as a function of rotor slot width is accepted as the main factor for choosing the rational rotor teeth zone geometrical dimensions considering the maximum borehole medium temperature and the parameters of the concrete supply circuit. Ill. 1, bibl. 6 (in English; summaries in English, Russian and Lithuanian).